Pyridazine doped g-C3N4 with nitrogen defects and spongy structure for efficient tetracycline photodegradation and photocatalytic H2 evolution. (November 2022) - Zhan, Xiaohui; Zhao, Yue; Sun, Yanping; Lei, Chen; Wang, He; Shi, Huixiang
Abstract: In this study, with thiourea and 3-aminopyridazine as precursors, the graphite-phase carbon nitride (ACN-x) with nitrogen defects and sponge structure is prepared via the introduction of the benzene-like ring structure of pyridazine replacing a "melem" group through hydrothermal procedure combined with calcination. It is made possible by the attraction of three hydrogen bond receptors for 3-aminopyrazine to lone pair electrons on the "melem" molecule. The remarkable extensively photocatalytic activity can be attributed to three effects of the introduction of 3-aminopyridazine: (i)formation of nitrogen defects between adjacent tri-s-triazine groups; (ii)formation of effective charge transfer channels within the tri-s-triazine group; (iii)the spongy structure exposed abundant amino groups(-NH3 ) at edge sites, combining with the internal amino group and as hole stabilizer to prolong the excited state life of photocatalyst. The photogenerated carrier migration and separation efficiency improved effectively through the tuning synergy. As a result, ACN-x exhibits excellent photocatalytic activity, with hydrogen production efficiency of up to 11331.74 μmol g −1  h −1, which is approximately 94.5 times that of the pristine g-C3 N4 (119.88 μmol g −1  h −1 ). The degradation constants of TC and RhB are 0.0498min −1 and 0.129min −1, which are 3.32 and 6.35 times of the pristine g-C3 N4, respectively. The TC degradation in different initial concentrations, pH, dissolved organic matter concentrations, and water sources is conducted to prove the environmental adaptability of the ACN-x system. The mechanism of the system indicates that ·O2 − plays an important role, and the ·OH and h + play a minor role in the TC photocatalytic degradation. Finally, the TC degradation possible pathway is proposed. Graphical abstract: Image 1 Highlights: The three hydrogen bond receptors and lone pair electrons allow the formation of new structures. Formation of nitrogen vacancies and effective charge transfer channels. The spongy structure exposed abundant amino groups at edge sites. The catalyst shows significantly enhanced photocatalytic activity in H2 production and TC degradation.